Socioscientific modelling as an approach towards justice-centred science pedagogy (UCL Press, 2023)
Justice-centred science pedagogy has been suggested as an effective framework for supporting teachers in bringing in culturally relevant pedagogy to their science classrooms; however, limited instructional tools exist that introduce social dimensions of science in ways teachers feel confident navigating. In this article, we add to the justice-centred science pedagogy framework by offering tools to make sense of science and social factors and introduce socioscientific modelling as an instructional strategy for attending to social dimensions of science in ways that align with justice-centred science pedagogy. Socioscientific modelling offers an inclusive, culturally responsive approach to education in science, technology, engineering, the arts and mathematics through welcoming students' diverse repertoires of personal and community knowledge and linking disciplinary knowledge with social dimensions. In this way, students can come to view content knowledge as a tool for making sense of inequitable systems and societal injustices. Using data from an exploratory study conducted in summer 2022, we present emerging evidence of how this type of modelling has shown students to demonstrate profound insight into social justice science issues, construct understandings that are personally meaningful and engage in sophisticated reasoning. We conclude with future considerations for the field.